PRIMARY NON-ESSENTIAL CUTIS VERTICIS GYRATA: REPORT OF A CASE - Ayaz, Saeed Bin; Matee, Sumeera; Bashir, Uzma; Malik, Riffat (Journal of Postgraduate Medical Institute, 2018)
Cutis verticis gyrata (CVG) is a rare transformation of the scalp characterized by ridges and furrows resembling surface of the brain. It has primary and second- ary types. Patients with primary CVG have normal skin and does not have an underlying pathological process. It is further subdivided into non-essential CVG and essential CVG based on the presence or absence of ophthalmological ab- normalities or neuropsychiatric problems such as mental retardation, cerebral palsy, schizophrenia or epilepsy. The secondary CVG is always a manifestation of an underlying inflammatory, neoplastic or a systemic disorder. We report here a case of cerebral palsy in a 16-year-old boy who presented with fourteen months' history of progressive deformity of head and face and was diagnosed as primary non-essential CVG.